2021
DOI: 10.3389/fphar.2021.683335
|View full text |Cite
|
Sign up to set email alerts
|

Follistatin Attenuates Myocardial Fibrosis in Diabetic Cardiomyopathy via the TGF-β–Smad3 Pathway

Abstract: Follistatin (FST) is an endogenous protein that irreversibly inhibits TGF-β superfamily members and plays an anti-fibrotic role in other diseases. However, the role of FST in diabetic cardiomyopathy remains unclear. In this study, we investigated the effects of FST on diabetic cardiomyopathy. The expression of FST was downregulated in the hearts of db/db mice. Remarkably, overexpressing FST efficiently protected against cardiac dysfunction. In addition, overexpression of FST promoted cardiac hypertrophy with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…Myocardial fibrosis is an important pathological feature of DCM. We also confirmed that fibrosis plays a role in the development of diabetic cardiomyopathy, as evidenced by the accumulation of collagen in the myocardial interstitial and perivascular region in the heart tissues of DCM rats, as well as the increase in transcription and protein expression of Col1, Col3, α-SMA, and TGF-β1 both in vivo and in vitro , findings that were in line with previous studies ( Huynh et al, 2014 ; Wang Y. H. et al, 2021b ). The abovementioned effects were significantly attenuated with NOX1 inhibition, and further enhanced with NOX1 overexpression.…”
Section: Discussionsupporting
confidence: 92%
“…Myocardial fibrosis is an important pathological feature of DCM. We also confirmed that fibrosis plays a role in the development of diabetic cardiomyopathy, as evidenced by the accumulation of collagen in the myocardial interstitial and perivascular region in the heart tissues of DCM rats, as well as the increase in transcription and protein expression of Col1, Col3, α-SMA, and TGF-β1 both in vivo and in vitro , findings that were in line with previous studies ( Huynh et al, 2014 ; Wang Y. H. et al, 2021b ). The abovementioned effects were significantly attenuated with NOX1 inhibition, and further enhanced with NOX1 overexpression.…”
Section: Discussionsupporting
confidence: 92%
“…Our data also support an observation in a randomized control trial and other rat models of DCM in which ALA administration prevented an increase in heart mitochondrial ROS production and effectively enhanced SOD activity and GSH content of myocardial mitochondria as well as decreased collagen deposition and TGF-β1 and mitochondria-dependent cardiac apoptosis ( Midaoui et al, 2003 ; Li et al, 2009 ; Lee J. E. et al, 2012 ; Hegazy et al, 2013 ). ROS promotes development of cardiac fibrosis in DCM by upregulating TGF-β1 and its downstream proteins Smad2 and 3 ( Purnomo et al, 2013 ; Wang et al, 2019 ; Wang et al, 2021 ) as was also observed in the present study. Moreover, Micheloudes et al (2011) reported that overexpression of TGF-β1 resulted in increased ROS-induced oxidative stress via increased expression of NADPH oxidase 4 (NOX4; a major modulator of ROS-related fibrosis) and decreased the activity of the mitochondrial antioxidant manganese-dependent superoxide dismutase (MnSOD).…”
Section: Discussionsupporting
confidence: 88%
“…Among these mechanisms, ROS-induced oxidative stress has received significant experimental attention as the unifying contributing factor in DCM development and progression ( Kakkar et al, 1995 ; Ghosh et al, 2004 ; Hamblin et al, 2007 ; Singh et al, 2008 ; Das et al, 2012 ; Tocchetti et al, 2015 ). Burgeoning evidence also shows that ROS-induced oxidative stress contributes to development of cardiac fibrosis in DCM by upregulating the expression of transforming growth factor-beta 1 (TGF-β1; a central mediator of cardiac fibrosis) ( Purnomo et al, 2013 ; Zhang et al, 2018; Wang et al, 2019 ; Wang et al, 2021 ). TGF-β1 induces remodeling and fibrosis in cardiac tissue and other tissues through activation of its downstream effector proteins referred to as Smads, which include Smad 2/3, Smad 4 and other Smads.…”
Section: Introductionmentioning
confidence: 99%
“… 45 A recent study found that FST could downregulate the Akt pathway in cardiocytes. 46 Thus, we assumed that mTOR was a key factor underlying how FST regulated lipid synthesis. We found that FST was a negative regulator of Akt and mTOR signaling in hepatic lipid synthesis.…”
Section: Discussionmentioning
confidence: 99%